Agro-manufactured export prices, wages and unemployment - Porto, Guido G. (The World Bank, 2008)
This paper estimates the impacts of world agricultural trade liberalization on wages, employment and unemployment in Argentina, a country with positive net agricultural exports and high unemployment rates. In the estimation of these wage and unemployment responses, the empirical model allows for individual labor supply responses and for adjustment costs in labor demand. The findings show that a 10 percent increase in the price of agricultural exports would cause an increase in the Argentine employment probability of 1.36 percentage points, matched by a decline in the unemployment probability of 0.75 percentage points and an increase in labor market participation of 0.61 percentage points. Further, the unemployment rate would decline by 1.23 percentage points (by almost 10 percent). Expected wages would increase by 10.3 percent, an effect that is mostly driven by higher employment probabilities. This indicates that the bulk of the impacts of trade reforms originates in household responses in the presence of adjustment costs, and that failure to account for them may lead to significant biases in the welfare evaluation of trade policy